Does Application of Artificial Intelligence Influence Carbon Emissions - Disha Rai; Omkar Rahangdale (International Journal of Environmental Noise and Pollution Control, 2024)
Due to the Paris Agreement, an increasing number of nations have made commitments and are actively trying to meet the net zero emission objective by the middle of the century. India has committed to a set target for intense carbon peaking by the year 2030, and to take a step towards carbon neutrality and try to reduce the emission by 45 per cent. It also committed to achieving about half (50 percent) of the cumulative electric grid capacity. India is one of the largest developing economies and ranks third among the 10 top carbon-emitting countries, but it does not regularly report emission statistics, making tracking seem to be a difficult task.
Keywords: Transportation, energy conservation, policymakers; artificial intelligence; carbon emission